Application of CISG in Arbitration: A Combined Procedure or Parallel Procedure? - Md. Habib Alam (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
CISG and arbitration are connected with each other. They may work through a combined or parallel procedure. Globalization of trade desires uniformity in trade. For uniformity of trade, we require uniform law. The arbitration may not work to make it uniform, but choosing any uniform law (i.e. CISG), it may lead to deal a particular arbitration in the international standard. The international standard may be maintained while considering the uniform law. Choosing uniform law (i.e. CISG), it may minimize the risk of wrong interpretation and put the arbitral parties on “equal footing”. Parties may consider CISG as the applicable law in their arbitral agreements. As of 13 February 2021, 94 states signed the United Nations Convention on Contracts for the International Sale of Goods 1980 (CISG). The frontline trading states like the USA, Australia, Israel, Canada, China, Germany, France, Russia, and Japan are contracting states of CISG. This research emphasizes providing guidelines as to how parties may apply CISG into their arbitral agreements by maintaining the international standard.